Clinical estimation of the use of the hip and knee extensors during athletic movements using 2D video - Straub, R. K.; Horgan, A.; Powers, C. M. (Journal of Applied Biomechanics, 2021)
Given that increased use of the knee extensors relative to the hip extensors may contribute to various knee injuries, there is a need for a practical method to characterize movement behavior indicative of how individuals utilize the hip and knee extensors during dynamic tasks. The purpose of the current study was to determine whether the difference between sagittal plane trunk and tibia orientations obtained from 2D video (2D trunk-tibia) could be used to predict the average hip/knee extensor moment ratio during athletic movements. Thirty-nine healthy athletes (15 males and 24 females) performed 6 tasks (step down, drop jump, lateral shuffle, deceleration, triple hop, and side-step-cut). Lower-extremity kinetics (3D) and sagittal plane video (2D) were collected simultaneously. Linear regression analysis was performed to determine if the 2D trunk-tibia angle at peak knee flexion predicted the average hip/knee extensor moment ratio during the deceleration phase of each task. For each task, an increase in the 2D trunk-tibia angle predicted an increase in the average hip/knee extensor moment ratio when adjusted for body mass (all P<.013, R2=.17-.77). The 2D trunk-tibia angle represents a practical method to characterize movement behavior that is indicative of how individuals utilize the hip and knee extensors during dynamic tasks.